Vitamin B6 Supplementation and Premenstrual Syndrome In Adolescents - Munawaroh, Siti Raudah; Nurunniyah, Siti; Nurinda, Eva; Paramita, Dyah Pradnya; Aji, Arif Sabta; Kurniawati, Putri; Yugistyowati, Anafrin; Wahyuningsih (International Journal of Public Health Excellence (IJPHE), 2025)
Background: Many women experience physical discomfort during menstrual periods with symptoms of menstrual disorders, such as abdominal pain and emotional instability, including mood swings and depression. PMS decreases adolescent creativity and productivity. Vitamin B6 induces the production of serotonin, which is assumed to reduce PMS symptoms. Objective: To find out the effectiveness of vitamin B6 supplementation in reducing PMS symptoms and which symptoms are most responsive to Vitamin B6. Methods: We conducted quasi-experimental, randomised, blinded, and controlled trials. The intervention and control groups each consisted of 20 adolescent girls aged 15-17 years. Adolescent girls who experienced PMS were randomly divided into two groups: group A was given vitamin B6 supplementation, and group B was given a placebo. where the respondent does not know which group he belongs to. The modified Premenstrual Syndrome Questionnaire and Premenstrual Symptom Questionnaire were used to determine the severity of PMS before and after the intervention. The data was analysed with a T-test. Initially, 154 girls were screened using an initial questionnaire, of which 142 were known to have PMS. 40 adolescent girls were randomly assigned to either a vitamin B6 group or a placebo. Results: There was a significant difference in the severity of PMS before and after in the group given vitamin B6 supplementation intervention with a P value of ≤ 0.05. The change in the severity score was the most in type D PMS. Conclusion: Vitamin B6 supplementation has an effect in reducing PMS. The largest score decline was in type D (depression), followed by type A (anxiety). Therefore, vitamin B6 may be recommended as a supplement for adolescent girls who experience PMS.